2013
DOI: 10.1186/1471-2369-14-37
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between preoperative creatinine clearance and outcomes for patients undergoing liver transplantation: a retrospective observational study

Abstract: BackgroundRenal failure with following continuous renal replacement therapy is a major clinical problem in liver transplant recipients, with reported incidences of 3% to 20%. Little is known about the significance of postoperative acute renal failure or acute-on-chronic renal failure to postoperative outcome in liver transplant recipients.MethodsIn this post hoc analysis we compared the mortality rates of 135 consecutive liver transplant recipients over 6 years in our center subject to their renal baseline con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…In the present study, we found an obvious difference between the AKI and non-AKI groups, regarding intraoperative blood loss, transfusion of blood products, cold or warm ischemia time, and total volume of intravenous infusion. These findings were consistent with previous studies 6 16 18 19 24 25 49 . However, regarding the duration of surgery, no significant difference was found between groups in our results, but some studies 17 32 53 inferred that this can be attributed to post-OLT AKI.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we found an obvious difference between the AKI and non-AKI groups, regarding intraoperative blood loss, transfusion of blood products, cold or warm ischemia time, and total volume of intravenous infusion. These findings were consistent with previous studies 6 16 18 19 24 25 49 . However, regarding the duration of surgery, no significant difference was found between groups in our results, but some studies 17 32 53 inferred that this can be attributed to post-OLT AKI.…”
Section: Discussionsupporting
confidence: 94%
“…Wenger et al . 25 have confirmed that many intraoperative data like duration of surgery and blood transfusion volume were independent factors contributing to post-OLT AKI. Here, we also observed a significant difference between groups in cold ischemia time (7 vs 6.17 h, P = 0.043), warm ischemia time (5 vs 5 min, P < 0.001), intraoperative blood loss (2500 vs 1600 mL, P < 0.001), red blood cells (2000 vs 1600 mL, P < 0.001), autologous blood cell transfusion (1225 vs 800 mL, P = 0.015), fresh frozen plasma (1850 vs 1450 mL, P < 0.001), and total intravenous infusion (6611.5 vs 5500 mL, P < 0.001).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Indications for ECMO were exactly as described previously [8] and for RRT the occurrence of risk, injury, failure, loss, end-stage renal disease (RIFLE) class 2 (injury), as we use routinely in our transplant programme [5,9]. …”
Section: Methodsmentioning
confidence: 99%
“…Wenger et al . showed that intraoperative blood transfusion was not associated with impaired kidney function in patients with normal baseline kidney function . Proteome analysis early after liver transplantation might be interesting to predict the development of CKD and to detect events induced either by the transplantation itself and/or the immunosuppressive regimen that can lead to CKD.…”
Section: Discussionmentioning
confidence: 99%